Flouting Maxim in "Spencer" Movie - Ni Made Verayanti Utami; Ni Nyoman Anyarani Puspaningrum (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
The purpose of the study is to identify the types of maxims that were flouted in Spencer movie. The movie tells about Princess Diana’s depression with her husband having an affair that she finds out during Christmas celebration with the Royal Family. The data was collected from the Spencer movie’s script that analysed using the cooperative principle theory by Grice (1989). The method that was applied in this research is descriptive qualitative method which also presented in informal and formal way. The result of this study showed that the four types of flouting maxim were performed in Spencer movie. There are 25 data (60%) for flouting maxim of relevance, 7 (17%) data in flouting quantity maxim, 6 data (14%) for flouting manner maxim, and 4 data (9%) in flouting quality maxim. The reasons why the flouting maxim can occur in this movie are: Diana often changes the subject because she has to behave as a princess, she cannot express her feelings and she insisted on something that is against the rules because she wants to show everyone that she is feeling broken inside that make her flouting the maxim of relevance. Diana also loves to make sarcasm about the rules in the palace making her flouting maxim the manner that makes the servers hard to understand. The servers always make Diana annoyed by telling a long story about why she has to follow the rules that make them flout the maxim of quantity. Diana sometimes lies so she can hide her feeling that blatantly disobeying the maxim of quality.